Accounting for the contribution of foreign direct investment in population health: A case study of Pakistan - Idrees, Sadia; Abu Bakar, Nor'Aznin (IJRSS, 2019)
This paper examines the impact of foreign direct investment (FDI) on life expectancy and infant mortality rate under-5 using time series data over the period of 1980–2017. We have applied unit root as well as co-integration tests to examine integrating properties of the variables and cointegration among the variables. Moreover, we apply the ARDL approach to measure the longrun and short-run impact of FDI on life expectancy and the infant mortality rate under-5. The empirical evidence confirms the presence of co-integration amid the variables. FDI increase population health measured by life expectancy and to reduce the infant mortality rate under-5 in the long-run.